OP- 10 - NON-STEROIDAL ANTI-INFLAMMATORY DRUGS: A COMPARATIVE ANALYSIS BETWEEN THE SPANISH AND LATINDILI NETWORKS - FERNANDO BESSONE; Ismael Alvarez Alvarez; Nelia Hernandez; Maria Isabel Schinoni; Inmaculada Medina Caliz; Hugo Tanno; Hao Niu; Maria Virginia Reggiardo; Federico Tanno; Gabriel Rifrani; Ezequiel Ridruejo; Manuel Mendizabal; et al. (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Background: Non-steroidal anti-inflammatory drugs (NSAIDs) represent a frequent cause of drug-induced liver injury (DILI). Aim: To compare demographics, clinical characteristics and outcomes of NSAIDs-induced liver injury between the LATINDILI and the Spanish DILI Registries. Patients / Materials and Methods: We analyzed 49 out of 468 LATINDILI cases (10,5%) and 82 out of 1254 Spanish DILI Registry cases (14%) induced by NSAIDs. Results and Discussion: In Spanish DILI cases, ibuprofen (33%), diclofenac (18%) and nimesulide (11%), were the most frequent culprit drugs, while diclofenac (33%), nimesulide (29%), ibuprofen (18%) and etoricoxib (10%) were the most common offending agents in LATINDILI cases. Surprisingly, etoricoxib was far more frequent in LATINDILI (10%) than in the Spanish DILI Registry (1.2%). Females predominated in Latin American cases (73%) compared to Spanish cases (47%) (p=0.011). Also, there was a trend towards a higher hospitalization rate in Spanish cases (63%) compared to LATINDILI cases (43%). (p=0.057). Notably, Hy's law showed to have drug-specific predictive value, with ibuprofen, nimesulide and etoricoxib associated with fatal outcomes, whereas DILI due to other AINEs did not have a worse outcome. We separately analyzed cases due to the most frequent culprits in each registry (ibuprofen and diclofenac). Notably, one patient died and one patient underwent liver transplantation linked to ibuprofen in the Spanish DILI Registry, while no death nor liver transplants were recorded in the LATINDILI due to ibuprofen. Likewise, no fatal outcome related to diclofenac were observed in these registries Conclusions: Differences in the incidence of DILI due to NSAIDs may reflect different prescribing patterns and public health policies in distinct countries. Ibuprofen can cause serious liver damage, and different doses in the OTC market and genetic factors may explain the differences in frequencies between registries. Hy's law prognostic performance varies between NSAIDs and is highest for nimesulide and ibuprofen. Etoricoxib DILI needs further investigation.